Comparative Study of Financial Planning According to the Sufficiency Economy Philosophy - Soonthonchai, Assoc. Prof. Dr. Phanita; Chotechoei, Asst. Prof. Dr. Nisara; Jaroenchai, Dr. Kittichai (Journal for Developing the Social and Community, 2019)
The objectives of this research were to study 1) to study the level of financial planning in accordance with Sufficiency Economy Philosophy, and 2) to compare financial planning based on sufficiency economy philosophy. This research was quantitative research. Sampling Group were people in Muenag district, Maha-sarakham province 400 sampling. Research instrument was questionnaires. Data were analyzed by percentage, mean, standard deviation and One-way ANOVA. The research found that 1) Overview of practices in Financial Planning in Sufficiency Economy was “high” (=3.83, S.D.=0.70). When considering each side, the order from the average to the least were the assessment of financial status according to the principle of Modesty (= 3.88, S.D.= 0.83), monitoring and improvement of financial planning based on knowledge and virtue (=3.83, S.D.= 0.92), determining personal financial goals based on rationality (= 3.82, S.D.= 0.85) and compliance with financial plans according to financial immunity principles (= 3.79, S.D. = 0.91) 2) Comparison of financial planning based on sufficiency economy philosophy of people in Muenag district, Maha-sarakham province, classified by age, educational level, occupation and status. Financial planning in accordance with the philosophy of Sufficiency Economy was different, statistically significant at the 0.05 level by gender and number of family members different. Financial planning in accordance with Sufficiency Economy Philosophy, not different statistically significant at the 0.05 level.